THE PRACTICE OF ENTREPRENEURIAL MADRASAH IN FOSTERING STUDENTS’ ENTREPRENEURIAL SPIRIT - Masturi; Khoirul Umam (Journal Of Islamic Education And Pesantren, 2022)
Entrepreneurship education has become a strategic necessity in responding to globalization and limited employment opportunities, particularly for Madrasah Aliyah students, many of whom do not continue to higher education. Madrasahs have significant potential to develop entrepreneurship education integrated with Islamic values through the Madrasah Entrepreneur approach. This study aims to examine and describe the practices of Madrasah Entrepreneur in fostering the entrepreneurial spirit of Madrasah Aliyah students. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation, and were analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing, with data credibility ensured through triangulation and member checking. The findings indicate that Madrasah Entrepreneur practices are implemented through the integration of entrepreneurial activities into learning processes, habituation, and the management of madrasah business units based on direct experiential learning. These practices contribute to the development of students’ entrepreneurial spirit, as reflected in increased independence, creativity, responsibility, initiative, and productive orientation. The discussion reveals that these findings align with entrepreneurship theory and experiential learning theory and are further strengthened by the integration of Islamic religious values. This study concludes that the Madrasah Entrepreneur model represents a relevant, contextual, and promising approach to entrepreneurship education in fostering the entrepreneurial spirit of Madrasah Aliyah students in a holistic manner.